The Impact of Drug Treatment Courts on Recovery: A Systematic Review - Ciska Wittouck; Anne Dekkers; Brice De Ruyver; Wouter Vanderplasschen; Freya Vander Laenen (The Scientific World Journal)
Introduction. Earlier reviews regarding the effectiveness of Drug Treatment Courts (DTCs) reported a reduction in reoffending and substance use. Although substance users suffer from other difficulties than drug use and judicial issues, none of these reviews focused on outcomes or effects of DTCs on drug-related life domains, such as social relationships, employment, or health. Therefor, the present paper aims to review the impact of adult DTCs on substance use and drug-related life domains. Method. Primary studies were systematically searched in Web of Knowledge. Observational and controlled evaluation studies of adult DTCs were considered eligible if substance use and/or drug-related life domains were measured. Results. Moderately positive results were found with respect to within-program substance use. Few studies used drug-related life domains as an outcome measure and most of them yielded no effects. Employment and family relations ameliorated when specific interventions were used. Discussion. DTCs yield beneficial outcomes and effects regarding within-program substance use. However, evidence regarding the impact of DTCs on post-program drug and alcohol use and on other drug-related life domains is scarce. These life domains and thus QoL possibly can be improved by DTCs if specifically targeted. Future research is warranted.